Elementary students practicing mindfulness a meeting of the minds - McIntyre, Alice 1956- (Mindfulness in education, 2019)
"This book examines how a group of ten-year-olds attending public school engaged in a mindfulness project over the course of an academic year. The young people's informative and inspiring dialogue, as well as their use of creative modes of expressions, reveals their varied understandings and lived experiences with mindfulness practices"--Provided by publisher.